1997
DOI: 10.1034/j.1600-0889.49.issue3.2.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-stabilization of the biosphere under global change: a tutorial geophysiological approach

Abstract: A 2‐dimensional extension of the simple Lovelock‐Watson model for geosphere‐biosphere feedback is introduced and discussed. Our enriched version also takes into account various pertinent physical, biological, and civilisatory processes like lateral heat transport, species competition, mutation, germination, and habitat fragmentation. The model is used as a caricature of the Earth System, which allows potential response mechanisms of the biosphere to environmental stress (as generated, e.g., by global warming o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 0 publications
1
29
0
1
Order By: Relevance
“…The next significant result to be repeated is that allowing albedo to mutate does not affect regulation, and may in some cases actually increase its range [4,5,6,7]. For this scenario we allowed albedo to take any value in the range [0.25, 0.75], corresponding to the full range from black to white.…”
Section: Repetition Of Existing Daisyworld Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The next significant result to be repeated is that allowing albedo to mutate does not affect regulation, and may in some cases actually increase its range [4,5,6,7]. For this scenario we allowed albedo to take any value in the range [0.25, 0.75], corresponding to the full range from black to white.…”
Section: Repetition Of Existing Daisyworld Resultsmentioning
confidence: 99%
“…We observed similar results to Lenton and Lovelock [10], in that regulation was observed to occur, but with a more gradual tailing in and tailing out than with the non-evolvable growth function. For completeness, we have also run the model with heat transfer between neighbouring patches [6], and found that the qualitative nature of the results is unchanged for all of the above scenarios. The exception is where the heat transfer is so efficient that there is no perceptible difference in temperature between patches; in this case there is no possiblity of a particular daisy species gaining a selective advantage over its competitors by altering its local temperature.…”
Section: Repetition Of Existing Daisyworld Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such observations can be seen as the starting point for the Gaia hypothesis which proposed that the Earth and its biota form a co-evolving, selfregulating system that is robust to perturbations (Lovelock, 1979). The initial Gaia hypothesis has developed with different studies considering it from different aspects such as evolution and natural selection (Lenton, 1998), theoretical ecology (von Bloh et al, 1997), dynamical systems (Lenton and van Oijen, 2002) and thermodynamics (Kleidon, 2004). It is now accepted that the possession of an atmosphere far from thermodynamic equilibrium is a sign of widespread life on Earth.…”
Section: "To Heat Are Also Due the Vast Movements Which Take Place Onmentioning
confidence: 99%